Origin and evolution of false brinelling and fretting corrosion under rolling conditions - Xin Jia; Lu Huang; Miao Sun; Wenbin Li (Friction)
Abstract Rolling bearings working in oscillating applications often suffer from false brinelling and fretting corrosion that limit their service life. At present, the study of oscillation-induced failures is primarily dominated by a large number of sliding and bench tests. However, most of the previous work are not able to fully describe the two closely related but different failure mechanisms. In this study, the origin and evolution of the two failures are thoroughly investigated under strictly controlled oscillating rolling conditions. The results show that failure evolves from false brinelling to fretting corrosion under dry friction conditions regardless of the oscillation amplitude. This process is accompanied by a large area peeling and serious oxidation, and the oxygen content increases from 2.50 wt% to 21.22 wt%. Oxidation is a crucial factor in the evolution of false brinelling into fretting corrosion. However, the distribution of microwear and oxygen content depend on the oscillation amplitude. Under lubrication conditions, the friction coefficient (COF) is smaller in the initial stage and led to local slip or transient instability of rolling elements. Therefore, the size of the wear marks and COF increased and appeared to be larger than those under a dry friction condition. However, grease can separate the contact surfaces, only surface deformation owing to false brinelling and slight damage at the roughness level occurred. The evolution of false brinelling and fretting corrosion is also closely related to residual stress. False brinelling often occurrs with residual stress accomulation, meanwhile, the residual stress increases from 120 to 300 MPa. When peeling occurs, residual stress is released. The failure pattern transformed from false brinelling to fretting corrosion and is accompanied by oxidation. So far, none of investigation is able to show satisfactory evolution of oscillating-induced failures, this study may contribute to more scientific understanding of rolling bearings against long-run reciprocating oscillating wear.